2001
DOI: 10.1093/ije/30.4.878
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus, hepatitis B, C and D in Bangladesh's trucking industry: prevalence and risk factors

Abstract: The results of the study illustrate the importance of educating health care practitioners about the dangers of unsterile injections, and of educating men in the trucking industry as well as their partners (CSW in particular) about the importance of condom use, especially in high-risk sexual contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 12 publications
3
27
1
Order By: Relevance
“…11,12 According to the 2003 national HIV and syphilis surveillance, HIV circulates at low levels among most of the high-risk groups but is highest among injecting drug users (4%) in central Bangladesh. 13 Studies conducted among truck drivers and helpers in Bangladesh revealed a high prevalence of sexual risk behaviors and certain STIs; 54% of the 388 truckers in the Tejgaon truck stand, one of the largest truck stands in Bangladesh, had sexual encounters with a commercial sex worker (CSW) in the past year, whereas 50% of the married males in the sample had sex with both a CSW and their wife during the same period.…”
mentioning
confidence: 99%
“…11,12 According to the 2003 national HIV and syphilis surveillance, HIV circulates at low levels among most of the high-risk groups but is highest among injecting drug users (4%) in central Bangladesh. 13 Studies conducted among truck drivers and helpers in Bangladesh revealed a high prevalence of sexual risk behaviors and certain STIs; 54% of the 388 truckers in the Tejgaon truck stand, one of the largest truck stands in Bangladesh, had sexual encounters with a commercial sex worker (CSW) in the past year, whereas 50% of the married males in the sample had sex with both a CSW and their wife during the same period.…”
mentioning
confidence: 99%
“…In this study, 318 (82.8%) of the participants were married whereas 194 (50.5%) were female and 124 (32.3%) were male. In regards to the occupation of the respondents, majority were housewives 108 (28 [16][17][18][19][20][21] .The higher rates among our study population could be attributed to the general lack of proper health care because of deprived socio-economic status (monthly household income of US $ 50) and less public health awareness about the transmission of Hepatitis B Virus infection as well as the lack of hepatitis B vaccination in the community.…”
Section: Resultsmentioning
confidence: 99%
“…5 The prevalence also corresponds to reports among highrisk group: 8.0% among drug addicts, 8 5.9% among truck drivers and helpers. 28 Lack of proper health care, lower socioeconomic status, less public awareness about the HBV transmission and lack of vaccination are proposed reason for high prevalence of HBV. High prevalence also reported in other high risk groups of Dhaka: 7.6% among women at a sexually transmitted disease (STD) clinic 9 , 8% among intravenous drug users (IDUs) 8 , 8.6% among surgically operated patients, 6 9.7% among commercial sex workers(CSWs), 7 19% among hepatitis patients 29 ; and 47% among hepatocellular carcinoma.…”
Section: Resultmentioning
confidence: 99%